PUBLIC RELATIONS MANAGEMENT STRATEGY TO CREATE SCHOOL BRANDING IN PASUNDAN 1 AND 2 MIDDLE SCHOOL IN BANDUNG CITY - Rahminawati, Nan (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
AbstractExcellent schools with the best quality cannot be separated from tight competition and school managerial abilities so that they come out as champions with the branding of their favorite schools. Branding strategy plays an important role in filling formal education towards globalization as is done by SMP Pasundan 1 and 2, Bandung City. This private school, provides future-oriented educational options that integrate the advantages of Sundanese culture, religion, and academic and non-academic achievements. This study explores how the implementation of planning, public relations strategy, and school branding by the two schools. This study analyzes the public relations managerial strategy in building an image through the concept of school branding with a descriptive qualitative approach, data obtained by interviews, observations, and literature studies. The results of the study revealed, the implementation of a public relations managerial strategy was carried out by school leaders, and school resources were able to build branding in the community. A systematic public relations management strategy through social media publicity, print, electronic, and educational communication packaging, to build a positive image of schools, students, and excellent schools which always have high public interest every year.